Effects of electronic cigarette on platelet and vascular function after one month of use. (25th November 2020) - Ikonomidis, I; Katogiannis, K; Kostelli, G; Kourea, K; Kyriakou, E; Kypraiou, A; Thymis, J; Benas, D; Triantafyllou, C; Andreadou, I; Tsoumani, M; Pavlidis, G; et al.
Abstract: Background and aims: Smoking is a major factor that contributes to the development of cardiovascular disease. Smoking cessation delays progress of coronary artery disease. Electronic cigarette is proposed as a bridge to smoking cessation. We examined its effects on platelet function after 1 month of use compared to tobacco smoking. Patients and methods: 40 current smokers (mean age 48 years±5) without cardiovascular disease were randomized to smoke either a conventional cigarette (conv-cig) or an electronic cigarette (e-cig) (electronic cigarette fluid with nicotine concentration of 12 mg/dL) for one month. All subjects smoked an electronic cigarette with nicotine concentration 12 mg/dL for one month. Measurements were performed at baseline and after one month of smoking the conventional or electronic cigarette. We measured a) perfused boundary region (PBR) of the sublingual arterial micro vessels (range 5–25 micrometers), a marker inversely related with glycocalyx thickness, b) pulse wave velocity (PWV), central systolic blood pressure (cSBP) and augmentation index (AIx), c) platelet function by two different methods, namely the novel Platelet Function Analyzer PFA-100 and the traditional Light Transmission Aggregometry (LTA) d) the exhaled CO level (parts per million-ppm) as a smoking status marker; and e) the plasma malondialdehyde (MDA) levels, as an oxidative stress burden index. Results: After 1 month of electronic smoking, we did not observe any significant change in platelet function and arterial stiffness (p>0.05 for all markers) with the exception of a reduction of MDA (1.22±0.1 vs 1.09±0.1 μmol/L, p=0.03) and exhaled CO; 14.9±0.7 vs 5.9±0.7 ppm, p<0.001. Conversely, after continuation of conventional cigarette smoking for a month, platelet function was further impaired as assessed by PFA [125, 5±31, 1 vs 152, 35±51, 4 U, p=0.047) and by LTA (epinephrine as stimulator) [59, 8%±16, 1 vs 35, 6%±19.1, p<0.001] and markers of arterial stiffness were deteriorated, as assessed by PWV (9, 5±2, 8 vs 10, 3±2, 9, p=0, 028) and by Aixc (8, 36±35, 9 vs 30, 4±21, 6, p=0, 004). Conclusions: Electronic Cigarette smoking has a neutral effect on platelet function and arterial stiffness markers compared to conventional tobacco smoking which further deteriorates platelet and vascular function during one moth of use. Funding Acknowledgement: Type of funding source: None